The analysis of code-mixing used on WhatsApp by English Language & Culture students at Universitas Widya Dharma Pontianak - Ritan Ritan; Windy Windy (Priviet Social Sciences Journal, 2025)
Code-mixing has become a common practice among bilingual and multilingual speakers, especially in informal digital communication, such as WhatsApp. This study aims to identify the types of code-mixing used by English Language and Culture students at Universitas Widya Dharma Pontianak and understand the reasons behind their language choice. This research applied a descriptive qualitative method using documentation of WhatsApp group messages and interviews with selected students. The data were analyzed using Muysken’s (2000) theory to classify the types of code-mixing and Bhatia and Ritchie’s (2006) theory to examine the reasons for its usage. The study found 42 messages containing code-mixing, with 29 cases of insertion, 5 cases of alternation, and 8 cases of congruent lexicalization, showing insertion as the most dominant type. The reasons for using code-mixing included participant roles and relationships, situational factors, message-intrinsic factors, social attitudes, language dominance, and security. These findings highlight how bilingual students mix languages in digital communication to express themselves effectively, reflecting their bilingual environment and the influence of social media on language practices.